Protective effect of ascorbic acid against renal injury induced by 3-chloropropane-1,2-diol-dipalmitate in rats - Tao Wei; Bohan Liu; Yi Chen; Chang Li (Renal Failure)
3-monochloropropane-1,2-diol esters (3-MCPDE) are a group of contaminants which are mainly formed during heat processing of edible oil and fat-based foods. The kidney is the primary target organ for the toxic effects of 3-MCPDE. 3-MCPD-di-palmitate exists in a variety of oils and fats, and is the most common and relatively high proportion of 3-MCPDE. In this study, we investigated the protective effect of ascorbic acid on 3-MCPD-di-palmitate-induced renal injury in rats. Thirty 8-week-old male Sprague-Dawley rats were randomly divided into 5 groups, namely control, 3-MCPD-di-palmitate (240 mg/kg·bw), 3-MCPD-di-palmitate (240 mg/kg·bw) + ascorbic acid (100 mg/kg·bw), 3-MCPD-di-palmitate (240 mg/kg·bw) + ascorbic acid (200 mg/kg·bw) and 3-MCPD-di-palmitate (240 mg/kg·bw) + ascorbic acid (500 mg/kg·bw). These treatments were administered via gavage for a duration of 4 weeks. The effects of ascorbic acid on 3-MCPDE-induced kidney injury in rats were investigated by evaluating the kidney index, renal function (BUN, CRE), renal histopathology, oxidative stress markers (ROS, GSH, MDA, and T-AOC), DNA oxidation marker (8-OHdG), and activities of Caspase 3 and 9. The results showed that the exposure to 3-MCPDE significantly increased the kidney index, BUN and CRE levels, ROS and MDA levels, 8-OHdG levels, and activities of Caspase 3 and 9, while decreasing GSH and T-AOC. The combined treatment with 3-MCPDE and ascorbic acid can effectively restore the aforementioned parameters. The present study concluded that ascorbic acid effectively attenuates the renal apoptosis and oxidative homeostasis induced by 3-MCPDE uptake thereby intervening in renal injury.